Les salafistes marocains et la reconfiguration politico-religieuse post-2011 : fluctuation entre (dé)politisation, radicalisation et intégration - Salim Hmimnat (L’Année du Maghreb)
The article examines the complex and fluctuant relationship which exists between the Moroccan regime and salafists from the 1970s until the ‘Arab Spring’. In each moment of this evolution, the regime opts for a pragmatic approach which consists in using this religious trend to meet pressing demands and priorities of a political and security nature. Ten years after breaking up with salafist groups, both quietists and jihadists, suspected to be responsible for the 2003 Casablanca attacks, the regime seeks henceforth to reconcile with salafis with the purpose to integrate them, or at least neutralise them, in the ongoing politico-religious reconfiguration process. Yet, this reconciliation, which aims to defuse the socio-political tensions and uncertainty the country has experienced in the aftermath of 2011 in addition to counterbalance the Islamists rising to power, is likely to challenge or even contradict certain ideological and doctrinal choices that have hitherto framed the religious policy since 2003.